Pengaruh Kontrol Diri, Moralitas, dan Religiusitas terhadap Pencegahan Kecurangan (Fraud) pada Pengelolaan Dana Desa Kecamatan Pagar Jati Kabupaten Bengkulu Tengah - Wahyu Dwi Aldestian; Lismawati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to evaluate and prove factors such as self-control, morality, and religiosity on how to prevent fraud in the management of village funds in Pagar Jati Sub-district, Central Bengkulu Regency. In this study using quantitative methods. The sampling technique used is purposive sampling and the type of data in this study is using primary data. The sample of this research is all village officials who work in the village government of Pagar Jati Subdistrict, Central Bengkulu Regency. The data collection technique used in this study was through distributing questionnaires. Technical analysis and hypothesis testing using Partial Least Square (PLS) tools using SmartPLS version 4.0 application software. The results of this study indicate that self-control, morality, religiosity have a positive and significant effect on fraud prevention in village fund management.